Strategi Orientasi Pada Industri Manufaktur Kabupaten dan Kota - Muchammad Aditya Ferdiansyah; Muhammad Yasin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study investigates the combined and interactive effect of Market Orientation, Entrepreneurial Orientation, and Technology Orientation on the business performance of manufacturing Small and Medium Enterprises (SMEs) in Indonesia. Employing a systematic literature review approach, the research integrates the conclusions of 75 relevant academic journal articles and industry reports. A method of narrative synthesis was utilized to interpret the relationships between these strategic orientations and firm performance. The findings reveal that all three orientations exert a meaningful and positive impact on SME performance. Entrepreneurial Orientation was identified as the key catalyst for innovation, Market Orientation as fundamental for achieving profitability, and Technology Orientation as a critical accelerator. However, the most profound contribution stems from the synergistic power of combining all three, which fosters a sustainable competitive advantage. Theoretically, this study enriches the current understanding of dynamic capabilities, demonstrating how they emerge from the internal orchestration of strategies to navigate turbulent market conditions. From a practical standpoint, it highlights the necessity for SMEs to transition from a siloed approach to cultivating an integrated portfolio of capabilities spanning market responsiveness, innovation, and technology. Furthermore, it recommends that government support shifts towards providing holistic, ecosystem-based programs rather than isolated technical training.